DRD3 (dopamine receptor D3) but not DRD2 activates autophagy through MTORC1 inhibition preserving protein synthesis. Issue 7 (2nd July 2020) - Barroso-Chinea, Pedro; Luis-Ravelo, Diego; Fumagallo-Reading, Felipe; Castro-Hernandez, Javier; Salas-Hernandez, Josmar; Rodriguez-Nuñez, Julia; Febles-Casquero, Alejandro; Cruz-Muros, Ignacio; Afonso-Oramas, Domingo; Abreu-Gonzalez, Pedro; Moratalla, Rosario; Millan, Mark J.; et al.
ABSTRACT: Growing evidence shows that autophagy is deficient in neurodegenerative and psychiatric diseases, and that its induction may have beneficial effects in these conditions. However, as autophagy shares signaling pathways with cell death and interferes with protein synthesis, prolonged use of autophagy inducers available nowadays is considered unwise. The search for novel autophagy inducers indicates that DRD2 (dopamine receptor 2)-DRD3 ligands may also activate autophagy, though critical aspects of the action mechanisms and effects of dopamine ligands on autophagy are still unknown. In order to shed light on this issue, DRD2- and DRD3- overexpressing cells and drd2 KO, drd3 KO and wild-type mice were treated with the DRD2-DRD3 agonist pramipexole. The results revealed that pramipexole induces autophagy through MTOR inhibition and a DRD3-dependent but DRD2-independent mechanism. DRD3 activated AMPK followed by inhibitory phosphorylation of RPTOR, MTORC1 and RPS6KB1 inhibition and ULK1 activation. Interestingly, despite RPS6KB1 inhibition, the activity of RPS6 was maintained through activation of the MAPK1/3-RPS6KA pathway, and the activity of MTORC1 kinase target EIF4EBP1 along with protein synthesis and cell viability, were also preserved. This pattern of autophagy through MTORC1 inhibition without suppression of protein synthesis, contrasts with that of direct allosteric and catalytic MTOR inhibitors and opens up new opportunities for G protein-coupled receptor ligands as autophagy inducers in the treatment of neurodegenerative and psychiatric diseases. Abbreviations: AKT/Protein kinase B: thymoma viral proto-oncogene 1; AMPK: AMP-activated protein kinase; BECN1: beclin 1; EGFP: enhanced green fluorescent protein; EIF4EBP1/4E-BP1: eukaryotic translation initiation factor 4E binding protein 1; GPCR; G protein-coupled receptor; GFP: green fluorescent protein; HEK: human embryonic kidney; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MAP2K/MEK: mitogen-activated protein kinase kinase; MAPK1/ERK2: mitogen-activated protein kinase 1; MAPK3/ERK1: mitogen-activated protein kinase 3; MDA: malonildialdehyde; MTOR: mechanistic target of rapamycin kinase; MTT: 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide; PPX: pramipexole; RPTOR/raptor: regulatory associated protein of MTOR, complex 1; RPS6: ribosomal protein S6; RPS6KA/p90S6K: ribosomal protein S6 kinase A; RPS6KB1/p70S6K: ribosomal protein S6 kinase B1; SQSTM1/p62: sequestosome 1; ULK1: unc-51 like autophagy activating kinase 1; WT: wild type.